Mastering English Together: Twinkl Educational Publishing Training for Teachers and Young Learners at KB & TK Al - Madani Malang - Ningsih, Fitria; Nikmah, Lailatul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study utilizes Twinkl.com (Twinkl Educational Publishing), an educational platform, to empower teachers and students by providing materials and resources, especially English for your learners (EYL). The methodology follows a service-learning (SL) approach, involving needs assessment, community engagement, curriculum development, teacher training, interactive student sessions, ongoing support, and monitoring. Research findings indicate initial unfamiliarity among teachers with Twinkl.com, but all find it convenient. Successes include increased teacher confidence and student enthusiasm, while challenges involve language English teachers and students' limitations with materials available in English. Overall, these findings show the positive impact of Twinkl.com on early childhood education, promising an enriched and dynamic English learning experience for young learners in preschool and kindergarten.